Chemical Peeling in Skin-Aging Patients: A Retrospective Study - Susanto, Ester Chateline; Setyaningrum, Trisniartami; Arifa Mustika; Astari, Linda (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Skin aging is a degenerative process that involves a decrease in the structure and function of skin cells and theextracellular matrix due to intrinsic and extrinsic factors. Chemical peeling is one of the skin aging treatments that involvesskin ablation using chemical agents. Purpose: To evaluate the profile of skin-aging patients treated with chemical peeling atthe Dermatology and Venereology Outpatient Unit of Dr. Soetomo General Hospital Surabaya from January throughDecember 2019. Methods: The data were obtained from patients' medical records through a total sampling technique, whichconsisted of age, gender, occupation, history taking, physical examination, diagnosis, therapeutic agents, follow-up frequency,and therapeutic result. Result: The study included 37 patients, the majority of whom were between the ages of 46 and 55(35.1%), female (100%), and private employees (32.4%). In history taking, patients' main complaint is dull skin (94.6%), withthe risk factor of sun exposure (97.3%) and the history of sunscreen usage (81.1%). Pigmentary changes were found in allpatients (100%). The most common diagnoses are photoaging Glogau II and Glogau III, found in 15 patients (40.5%),respectively. The common priming agents were sunscreen (97.3%), cleanser (94.6%), and 8% glycolic acid (75.7%). Themajority of patients (62.2%) received 20% glycolic acid as a peeling agent and sunscreen (86.5%) as a post-peeling agent.The majority of patients (43.2%) did not follow up. Glogau II photoaging (57.1%) was the main therapeutic result.Conclusion: Proper chemical peeling procedures and patients compliance are important factors to improve therapeuticoutcomes.